High irisin levels are associated with better glycemic control and bone health in children with Type 1 diabetes. (July 2018) - Faienza, Maria Felicia; Brunetti, Giacomina; Sanesi, Lorenzo; Colaianni, Graziana; Celi, Monica; Piacente, Laura; D'Amato, Gabriele; Schipani, Ernestina; Colucci, Silvia; Grano, Maria
Highlights: High irisin levels in childhood type 1 diabetes mellitus. Continuous subcutaneous insulin infusion is associated with higher irisin levels than multiple daily injections. The association of high irisin amounts with a better glycaemic control and bone health. Abstract: Aim: Irisin is a new peptide produced mainly by the skeletal muscle playing an important role both in glucose/energy homeostasis and bone metabolism. Childhood type 1 diabetes mellitus (T1DM) is associated with decreased bone mass. We aimed to evaluate irisin levels in TD1M children and their correlation with bone metabolism and glycaemic control. Methods: Ninety-six T1DM subjects (12.2 ± 4 years), 56 on multiple daily injections (MDI), 40 on continuous subcutaneous insulin infusion (CSII), and 34 controls were included in the study. Irisin and bone remodeling markers were quantified in sera from patients and controls. Bone mineral density (BMD) was evaluated by QUS. Results: Increased irisin levels were found in T1DM patients respect to controls (p < 0.001). With adjustment for age, irisin levels significantly correlated negatively with HbA1c% (r = −0.105, p < 0.001), years of diabetes (r = −0.07, p < 0.04), 25(OH)-Vitamin D (r = −0.175, p < 0.0001), and positively with BTT-Z-score (r = 0.088, p = 0.016), and osteocalcin (r = 0.059, p < 0.04). We detected the highest levels of irisin in CSII patients compared to MDI and controls (p < 0.001 and p < 0.007 respectively). Conclusions: We demonstrated high irisin levels in T1DM children and the association of highest irisin amounts to a better glycaemic control and bone health in TDM1 subjects on CSII.